Fiscal policy responses to COVID-19 in Switzerland: a high-frequency dataset on federal and sub-federal policy announcements in the first year of the pandemic - Vera Z. Eichenauer; Remo Gurtner; Furkan Oguz (Swiss Journal of Economics and Statistics)
Abstract The Swiss COVID-19 fiscal policy dataset includes detailed information on all fiscal support policies adopted in Switzerland in response to the COVID-19 pandemic. Covering the period from February 2020 to February 2021, the dataset includes both quantitative and textual information about nine types of fiscal policy instruments announced by local governments in one of Switzerland’s 26 cantons (regional jurisdictions) or at the national level. The data has been hand-coded and primarily collected from official sources, including government decrees, minutes from ministerial meetings, and press releases. The dataset contains 1330 policy observations, with data coded into up to 23 variables. It allows for the analysis of differences in COVID-19 fiscal support measures across regions, their timing, the political decision-makers, the types of policies, and further characteristics. This data offers valuable insights for answering research questions related to fiscal policy and its links to various social and economic phenomena.